HomeMaestro: Distributed monitoring and diagnosis of performance anomalies in home networks - Gkantsidis, Christos; Karagiannis, Thomas; Athanasopoulos, Elias; Raftopoulos, Elias; Key, Peter (2008)
Home networks are comprised of applications running over multiple wired and wireless devices competing for shared network resources. Despite all the devices operating in a single administrative domain in such networks, applications operate independently, and users cannot express or enforce policies. By studying multiple households’ network performance at the packet-level correlated with diaries capturing user experiences, we show that the lack of cooperation across applications leads to observable performance problems and associated user frustration. We describe HomeMaestro, a cooperative host-based system that monitors local and global application performance, and automatically detects contention for network resources. HomeMaestro is designed to manage home and small networks and requires no modification to routers, access points, applications, or protocols. At each host, it transparently monitors per-flow and per-process network usage statistics, such as throughput, RTT, and loss rates. We propose novel
MSR-TR-2008-161